2014
DOI: 10.1159/000368342
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Dependent Thalassemia in Northern Sarawak: A Molecular Study to Identify Different Genotypes in the Multi-Ethnic Groups and the Importance of Genomic Sequencing in Unstudied Populations

Abstract: Background: Although thalassemia is a genetic hemoglobinopathy in Malaysia, there is limited data on thalassemia mutations in the indigenous groups. This study aims to identify the types of globin gene mutations in transfusion-dependent patients in Northern Sarawak. Methods: Blood was collected from 32 patients from the Malay, Chinese, Kedayan, Bisayah, Kadazandusun, Tagal, and Bugis populations. The α- and β-globin gene mutations were characterized using DNA amplification and genomic sequencing. Results: Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…IVS‐I‐117 (G>A) was a rare mutation which was firstly reported in Indian population . And HBA2:c.95+5_95+28delGGCTCCCTCCCCTGCTCCGACCCG was only reported once in Malaysia . Interestingly, HBA2:c.184A>T(Lys>End) was a recently reported novel mutation which was also found by NGS in Guangdong Province, China .…”
Section: Discussionmentioning
confidence: 95%
“…IVS‐I‐117 (G>A) was a rare mutation which was firstly reported in Indian population . And HBA2:c.95+5_95+28delGGCTCCCTCCCCTGCTCCGACCCG was only reported once in Malaysia . Interestingly, HBA2:c.184A>T(Lys>End) was a recently reported novel mutation which was also found by NGS in Guangdong Province, China .…”
Section: Discussionmentioning
confidence: 95%
“…Hence, the survival rate of patients with thalassemia in Malaysia has improved 6 . With several molecular studies have been done previously in the East and West Malaysia, genetic heterogeneity is more observed in multiracial population in Malaysia with a diverse spectrum of alpha (α-), beta (β-) and delta (δ-) globin genes mutations among the patients with thalassemia syndromes [7][8][9][10][11] . Beta-thalassemia is due to decreased beta-globin chain synthesis of which, caused by a mutation in the HBB gene.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the HRM analysis developed for detection of the β-FIL deletion showed 100% specificity and sensitivity. As the Filipino β 0 -thalassaemia deletion was reported to be present in a high frequency in the indigenous groups in East Malaysia 7 8 9 , molecular screening for this defect should be implemented in order to prevent the birth of β-thalassaemia major children. It is even more pertinent that screening for the β-FIL deletion be carried out as the majority of these individuals are not aware that they are thalassaemia carriers due to their isolation from towns and limited medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Gap-PCR was performed to detect the α-SEA and β-FIL deletions using a Veriti thermal cycler (Applied Biosystems, USA). The total reaction volume for gap-PCR was 25 μl which contained 10X PCR buffer, 2.5 U Taq DNA polymerase (Fermentas, Germany), 800 μM of dNTP, 20 pmol for each primer, 2.5 mM magnesium chloride (MgCl 2 ) 7 9 . The cycling conditions for the α-SEA deletion involved 95 °C for 5 minutes, followed by 30 cycles of denaturation at 93 °C for 1 minute, annealing at 60 °C for 1 minute and extension at 72 °C for 1.5 minutes, and finally an extension step at 72 °C for 6 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation